Pea, Pisum sativum, and Its Anticancer Activity - Rungruangmaitree, Runchana; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Pisum sativum (Family: Fabaceae), as known as green pea or garden pea, has long been important in diet due to its content of fiber, protein, starch, trace elements, and many phytochemical substances. It has been shown to possess antibacterial, antidiabetic, antifungal, anti‑inflammatory, antihypercholesterolemia, and antioxidant activities and also shown anticancer property. Its nonnutritive biologically active components include alkaloids, flavonoids, glycosides, isoflavones, phenols, phytosterols, phytic acid, protease inhibitors, saponins, and tannins. This plant is rich in apigenin, hydroxybenzoic, hydroxycinnamic, luteolin, and quercetin, all of which have been reported to contribute to its remedial properties including anticarcinogenesis property. Based on established literature on the anticancer property of P. sativum and possible mode of action, this review article has focused to demonstrate that P. sativum could be further explored for the development of anticancer treatment.
Keywords: Anticancer; pea; Pisum sativum; plant; traditional medicine